Harm-reducing filter stick based on multifunctional metal organic framework and cigarette product
A porous filter rod is constructed by cross-linking multifunctional metal-organic framework materials with sodium alginate, which solves the shortcomings of existing cigarette filter rods in reducing tar and harmful components, achieves efficient filtration and environmentally friendly production, and is suitable for the preparation of low-harm cigarettes.
Patent Information
- Application Number
- CN202510997397.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-09-05
AI Technical Summary
Existing cigarette filter rods have shortcomings in reducing tar and harmful components, especially paper filter rods, which have a dry taste when smoking, poor pressure drop stability, and poor retention of phenolic components. At the same time, they are highly dependent on wood resources and cannot meet the demand for low-harm cigarettes.
By combining multifunctional metal-organic framework materials with the cross-linking reaction of sodium alginate and calcium ions, a porous filter rod is constructed through freeze-drying technology. The pore adsorption and functional group effects of MOF nanoparticles are utilized to achieve efficient filtration of harmful components such as tar and phenols.
It significantly reduces tar release and harmful components, improves smoking taste, reduces dependence on wood resources, meets environmental protection standards, and is suitable for large-scale production.
Smart Images

Figure CN120585124A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tobacco products, and in particular to a harm-reducing filter rod and a cigarette product based on a multifunctional metal-organic framework. Background Art
[0002] With the significant increase in public health awareness, the demand for less harmful cigarette products has become increasingly urgent. Tar is the main harmful component produced during cigarette combustion, and reducing its content is crucial to alleviating the harm of smoking to the human body.
[0003] Cigarette filter rods, a crucial component of cigarettes, are composed of filter material and forming paper, tightly bonded to the cigarette via tipping paper. Their core function is to filter smoke and prevent tobacco shreds from scattering. Their filtration mechanisms primarily include direct interception, inertial impact, and diffusion deposition. Currently, low-tar cigarettes on the market mostly use paper filter rods or paper-vinegar composite filter rods. Compared to traditional acetate filter rods, paper filter rods offer significant advantages: they are not only more biodegradable and more cost-effective, but also, at the same filtration pressure drop, they are more efficient at retaining tar and nicotine in the smoke. However, paper filter rods also have significant drawbacks: first, they can have a relatively dry, harsh taste, impacting user experience; second, they are less effective than acetate filter rods in retaining harmful components in the smoke, such as phenols, resulting in a "papery" flavor in the smoke; and third, the pressure drop stability of paper filter rods is poor, impacting their effectiveness. Furthermore, both acetate and paper filter rods rely primarily on wood as their fiber raw material. The dwindling global wood resources and growing awareness of environmental protection have made it urgent to find acetate substitutes and reduce reliance on wood resources. This will not only help alleviate the shortage of wood resources but also promote the sustainable development of the filter rod industry.
[0004] Metal-organic frameworks (MOFs), as an emerging porous material, show great potential for pollutant control due to their structural diversity and tunability. However, the application of MOF materials in filter rod preparation still faces many technical challenges, such as ensuring the stability and shape regularity of MOF materials and achieving efficient filtration.
[0005] Freeze-drying technology, also known as vacuum freeze-drying technology, is a method of drying materials under vacuum and low-temperature conditions. The principle is to pre-freeze the material at low temperatures, converting the moisture in the material into solid ice. Then, in a vacuum environment, the solid ice is directly sublimated into gaseous water vapor through heating, thereby removing the moisture from the material and achieving the purpose of drying. During the freeze-drying process, since the moisture in the material exists in the form of ice crystals, when the ice crystals sublime, they leave pores within the material, forming a porous structure. This porous structure greatly increases the specific surface area exposed to smoke aerosol particles, potentially achieving efficient filtration of harmful components in the smoke. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a harm-reducing filter rod and cigarette product based on a multifunctional metal-organic framework. By combining the adsorption properties of MOF materials with the advantages of a homogeneous porous structure, efficient filtration of cigarette smoke aerosol particles can be achieved, meeting consumers' demand for low-harm tobacco products and opening up a new path for the innovation and development of cigarette filter rod technology.
[0007] The technical problem to be solved by the present invention is achieved through the following technical solutions:
[0008] A method for preparing a harm reduction filter rod based on a multifunctional metal-organic framework comprises the following steps:
[0009] (1) Preparation of sodium alginate solution: Weigh sodium alginate and dissolve it in deionized water, stirring until completely dissolved to form a sodium alginate aqueous solution with a mass fraction of 3% to 5%;
[0010] (2) Preparation of calcium chloride solution: Weigh calcium chloride and dissolve it in ethanol, stirring until completely dissolved to form a calcium chloride ethanol solution with a mass concentration of 30-50 g / L;
[0011] (3) Preparation of metal-organic framework materials: Nanoparticles were added to a sodium alginate aqueous solution in batches under 20-30 kHz high-frequency ultrasonic conditions and ultrasonically dispersed for 30 minutes to form a uniform mixed solution;
[0012] (4) Freeze molding: the solution is poured into a cylindrical mold, frozen in liquid nitrogen to form ice solid, and then the mold is peeled off after being left at room temperature;
[0013] (5) Freeze-drying and cross-linking: After 24 hours of freeze-drying, the product was immersed in a calcium chloride ethanol solution for cross-linking for 6 to 12 hours, and then washed with ethanol until no Ca2 + The residue is finally dried at 40℃ under vacuum conditions for 12 to 24 hours to obtain the harm reduction filter stick.
[0014] Preferably, in the above technical solution, the nanoparticles are MOF-Zn nanoparticles and / or ZIF-Zn nanoparticles.
[0015] Preferably, in the above technical solution, the preparation method of the MOF-Zn nanoparticles is:
[0016] A certain amount of 2,5-dihydroxyterephthalic acid and zinc nitrate hexahydrate were dissolved in 100 mL of N,N-dimethylformamide (DMF). After ultrasonic treatment, 5 mL of water was added and the mixture was transferred to a hydrothermal autoclave for reaction at 110-120°C for 24 hours. After cooling, the mixture was washed with DMF and methanol three times each, then soaked in methanol for three days. Finally, the mixture was vacuum-dried at 150°C for one hour. The molar ratio of zinc nitrate to 2,5-dihydroxyterephthalic acid was 1:3-5.
[0017] Preferably, in the above technical solution, the preparation method of the ZIF-Zn nanoparticles is:
[0018] A certain amount of zinc nitrate hexahydrate and 2-methylimidazole were weighed and dissolved in water and methanol respectively. The two solutions were mixed under stirring and reacted for 3 hours. The product was collected by centrifugation, washed with water and methanol three times each, and dried in vacuo at 85°C for 1 hour. The molar ratio of zinc nitrate to 2-methylimidazole was 1:2-8, and the volume ratio of water to methanol was 1:10.
[0019] A harm-reducing filter rod based on a multifunctional metal-organic framework is prepared according to the above-mentioned preparation method.
[0020] A cigarette product comprises a harm-reducing filter rod.
[0021] Application of a harm-reducing filter rod in the preparation of low-tar cigarettes.
[0022] Preferably, in the above technical solution, the multi-level pore structure of the filter rod and the synergistic effect of the functional groups are utilized to achieve efficient retention of harmful components such as tar, phenols and aldehydes in the flue gas through pore adsorption, molecular sieving and chemical bonding.
[0023] The above technical solution of the present invention has the following beneficial effects:
[0024] (1) The present invention uses metal organic framework nanoparticles as the core part of the filter rod, and achieves efficient filtration of smoke aerosol particles by virtue of its structural diversity, unique pore structure and large specific surface area;
[0025] (2) Using the controlled cross-linking reaction of sodium alginate and calcium ions to construct a three-dimensional mesh filter rod skeleton to replace traditional acetate fiber can not only significantly reduce dependence on wood resources and promote the low-carbon transformation of the filter rod industry, but also the environmentally friendly bio-based materials meet the latest domestic environmental protection standards, helping the tobacco industry achieve the goal of "carbon neutrality".
[0026] (3) During the freeze-drying process of the filter rod containing the MOF particle segment, the water directly sublimates, resulting in the formation of a large number of micron-sized pores inside the base rod, which significantly increases the specific surface area. This structure not only prolongs the residence time of the smoke aerosol particles in the pores, but also improves the capture efficiency of harmful components such as tar through the "cage effect". In addition, sodium alginate molecules are rich in functional groups such as carboxyl (-COOH) and hydroxyl (-OH) exposed on the surface. These groups can form hydrogen bonds with polar molecules in tar (such as phenols), further promoting the reduction of harmful components such as tar.
[0027] (4) The filter rod of the present invention has a simple structural design, is easy to process and manufacture, and has a relatively low cost, making it suitable for large-scale industrial production;
[0028] (5) The filter rod of the present invention can also be used in the preparation of low-tar cigarettes, effectively reducing the tar content in cigarettes and meeting consumers' demand for low-harm tobacco products. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Preparation of coaxial composite filter rod and cigarette sample, a. Visual image of MOF-Zn+SA filter rod, b. Electron microscope image of MOF-Zn+SA filter rod. DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that unless otherwise specifically stated, the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention.
[0031] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods. The materials and reagents used are all commercially available unless otherwise specified. The equipment used in the experiments are all well known to those skilled in the art unless otherwise specified.
[0032] 1. Preparation of multifunctional metal-organic framework materials:
[0033] a. Preparation of MOF-Zn: In a 400 mL beaker, 5 mmol of 2,5-dihydroxyterephthalic acid and 1.5 mmol of zinc nitrate tetrahydrate were dissolved in 100 mL of N,N-dimethylformamide (DMF) and sonicated. 5 mL of water was then added to the solution. The mixed solution was then transferred to a hydrothermal reactor and hydrothermally reacted at 110-120°C for 24 hours. After cooling to room temperature, the mother liquor was poured out, and the product was washed three times with DMF and then three times with methanol. The product was then immersed in methanol. The methanol solvent was changed daily for the next three days. Finally, the product was vacuum dried at 150°C for 1 hour.
[0034] b. Preparation of ZIF-Zn: Dissolve 4 mmol of zinc nitrate hexahydrate in 8 mL of water and 32 mmol of 2-methylimidazole in 80 mL of methanol. The two solutions were then slowly mixed under sufficient stirring and stirred for 3 hours to ensure complete reaction. After the reaction, the resulting white powder was collected by centrifugation. The white powder was washed three times with water and methanol, respectively, and then dried in a vacuum environment at 85°C for 1 hour.
[0035] 2. Preparation of sodium alginate aqueous solution (SA)
[0036] Weigh a certain amount of sodium alginate into a beaker, add a certain amount of deionized water, and stir until the sodium alginate is completely dissolved. The mass fraction of the sodium alginate is 3% to 5%.
[0037] 3. Take a certain amount of calcium chloride in a beaker, add a certain amount of ethanol, and stir until the calcium chloride is completely dissolved. The mass concentration of calcium chloride is 30-50g / L.
[0038] 4. Preparation of composite base rod
[0039] (1) Preparation of sodium alginate-based rods
[0040] Sodium alginate solution was added to a specific cylindrical mold, which was then frozen in liquid nitrogen to obtain an ice solid in the same shape as the mold. The solid was then placed in the air for a period of time and the glass template was peeled off. After 24 hours of freeze drying, it was immersed in an ethanol solution containing calcium chloride for 6-12 hours, and then washed with ethanol several times until no calcium ions (Ca2 + Finally, the alginate rods were obtained by vacuum drying at 40°C for 12 to 24 hours.
[0041] (2) Preparation of metal organic framework compound + sodium alginate based rods
[0042] The metal organic framework nanoparticles were uniformly dispersed in a sodium alginate aqueous solution under high-frequency ultrasonic treatment (20 kHz). The resulting metal organic framework@SA solution was then added to a specific cylindrical mold. After freezing it in liquid nitrogen, an ice solid with the same shape as the mold was obtained. The ice solid was then placed in air for a period of time and the mold was peeled off. After 24 hours of freeze drying, it was immersed in an ethanol solution containing calcium chloride for 6-12 hours and then washed with ethanol several times until no calcium ions (Ca2 + ) residue, and finally, vacuum drying at 40°C for 12 to 24 hours to obtain the metal organic framework compound + sodium alginate-based rod.
[0043] 5. Production of filter rods and cigarette products
[0044] Using a filter rod making machine, based on cigarettes of a certain specification, filter rod samples are prepared on the same machine, and the filter rods are used to roll cigarette samples on the same machine.
[0045] Comparative Example
[0046] Weigh 50 g of sodium alginate into a beaker, add 1000 mL of deionized water, and stir until the sodium alginate is completely dissolved. The mass fraction of sodium alginate is 4.76%.
[0047] Take 50g of calcium chloride in a beaker, add 1000mL of ethanol, and stir until the calcium chloride is completely dissolved. The mass concentration of calcium chloride is 50g / L.
[0048] The prepared sodium alginate solution was added to a cylindrical mold with a circumference of 16.9 mm and a bottom. After freezing in liquid nitrogen, an ice solid with the same shape as the mold was obtained. The ice solid was then placed in the air for a period of time and the mold was peeled off. After 24 hours of freeze drying, it was immersed in an ethanol solution containing calcium chloride for 12 hours and then washed with ethanol several times until no calcium ions (Ca2 + Finally, the mixture was dried under vacuum at 40°C for 12 to 24 hours to obtain a sodium alginate-based rod (SA filter rod).
[0049] Example 1
[0050] Weigh 50 g of sodium alginate into a beaker, add 1000 mL of deionized water, and stir until the sodium alginate is completely dissolved. The mass fraction of sodium alginate is 4.76%.
[0051] 15 g of MOF-Zn nanoparticles were weighed and added to the above sodium alginate aqueous solution in batches under high-frequency ultrasonic treatment (20-30 kHz). After the addition was completed, ultrasonic dispersion was continued for 30 min to ensure that the MOF-Zn nanoparticles were evenly dispersed to obtain a MOF-Zn@SA solution.
[0052] Take 30g of calcium chloride in a beaker, add 1000mL of ethanol, and stir until the calcium chloride is completely dissolved. The mass concentration of calcium chloride is 30g / L.
[0053] The MOF-Zn@SA solution was added to a cylindrical mold with a circumference of 16.9 mm and a bottom. After freezing in liquid nitrogen, an ice solid with the same shape as the mold was obtained. The ice solid was then placed in air for a period of time and the mold was peeled off. After 24 hours of freeze drying, it was immersed in an ethanol solution containing calcium chloride for 12 hours and then washed with ethanol several times until no calcium ions (Ca2 +Finally, the mixture was vacuum-dried at 40°C for 12 to 24 hours to obtain a MOF-Zn+SA base rod, in which the weight of MOF-Zn nanoparticles accounted for approximately 30%.
[0054] Example 2
[0055] Weigh 50 g of sodium alginate into a beaker, add 1000 mL of deionized water, and stir until the sodium alginate is completely dissolved. The mass fraction of sodium alginate is 4.76%.
[0056] Weigh 25 g of MOF-Zn nanoparticles and add them to the above sodium alginate aqueous solution in batches under high-frequency ultrasonic treatment (20-30 kHz). After the addition is completed, continue ultrasonic dispersion for 30 minutes to ensure that the MOF-Zn nanoparticles are evenly dispersed to obtain a MOF-Zn@SA solution.
[0057] Take 40g of calcium chloride in a beaker, add 1000mL of ethanol, and stir until the calcium chloride is completely dissolved. The mass concentration of calcium chloride is 40g / L.
[0058] The MOF-Zn@SA solution was added to a cylindrical mold with a circumference of 16.9 mm and a bottom. After freezing in liquid nitrogen, an ice solid with the same shape as the mold was obtained. The ice solid was then placed in air for a period of time and the mold was peeled off. After 24 hours of freeze drying, it was immersed in an ethanol solution containing calcium chloride for 12 hours and then washed with ethanol several times until no calcium ions (Ca) were detected. 2+ Finally, the mixture was vacuum-dried at 40°C for 12 to 24 hours to obtain a MOF-Zn+SA base rod, in which the weight of MOF-Zn nanoparticles accounted for approximately 50%.
[0059] Example 3
[0060] Weigh 50 g of sodium alginate into a beaker, add 1000 mL of deionized water, and stir until the sodium alginate is completely dissolved. The mass fraction of sodium alginate is 4.76%.
[0061] 15 g of ZIF-Zn nanoparticles were weighed and added to the above sodium alginate aqueous solution in batches under high-frequency ultrasonic treatment (20-30 kHz). After the addition was completed, ultrasonic dispersion was continued for 30 min to ensure that the ZIF-Zn nanoparticles were evenly dispersed to obtain a ZIF-Zn@SA solution.
[0062] Take 40g of calcium chloride in a beaker, add 1000mL of ethanol, and stir until the calcium chloride is completely dissolved. The mass concentration of calcium chloride is 40g / L.
[0063] The ZIF-Zn@SA solution was added to a cylindrical mold with a circumference of 16.9 mm and a bottom. After freezing in liquid nitrogen, an ice solid with the same shape as the mold was obtained. The ice solid was then left in the air for a period of time and the mold was peeled off. After 24 hours of freeze drying, it was immersed in an ethanol solution containing calcium chloride for 12 hours and then washed with ethanol several times until no calcium ions (Ca2 + Finally, the ZIF-Zn+SA base rod is obtained by vacuum drying at 40°C for 12 to 24 hours. The ZIF-Zn nanoparticles account for about 30% by weight of the base rod.
[0064] Example 4
[0065] Weigh 50 g of sodium alginate into a beaker, add 1000 mL of deionized water, and stir until the sodium alginate is completely dissolved. The mass fraction of sodium alginate is 4.76%.
[0066] 30 g of ZIF-Zn nanoparticles were weighed and added to the above sodium alginate aqueous solution in batches under high-frequency ultrasonic treatment (20-30 kHz). After the addition was completed, ultrasonic dispersion was continued for 30 min to ensure that the ZIF-Zn nanoparticles were evenly dispersed to obtain a ZIF-Zn@SA solution.
[0067] Take 40g of calcium chloride in a beaker, add 1000mL of ethanol, and stir until the calcium chloride is completely dissolved. The mass concentration of calcium chloride is 40g / L.
[0068] The ZIF-Zn@SA solution was added to a cylindrical mold with a circumference of 16.9 mm and a bottom. After freezing in liquid nitrogen, an ice solid with the same shape as the mold was obtained. The ice solid was then left in air for a period of time and the mold was peeled off. After 24 hours of freeze drying, it was immersed in an ethanol solution containing calcium chloride for 12 hours and then washed with ethanol several times until no calcium ions (Ca2 + Finally, the mixture was vacuum dried at 40°C for 12 to 24 hours to obtain a ZIF-Zn+SA base rod, in which the mass of the ZIF-Zn nanoparticles accounted for approximately 60%.
[0069] Example 5
[0070] Weigh 50 g of sodium alginate into a beaker, add 1000 mL of deionized water, and stir until the sodium alginate is completely dissolved. The mass fraction of sodium alginate is 4.76%.
[0071] 15 g of MOF-Zn nanoparticles were weighed and added to the above sodium alginate aqueous solution in batches under high-frequency ultrasonic treatment (20-30 kHz). After the addition was completed, ultrasonic dispersion was continued for 30 min to ensure that the MOF-Zn nanoparticles were evenly dispersed to obtain a MOF-Zn@SA solution.
[0072] 15 g of ZIF-Zn nanoparticles were weighed and added to the above sodium alginate aqueous solution in batches under high-frequency ultrasonic treatment (20-30 kHz). After the addition was completed, ultrasonic dispersion was continued for 30 min to ensure that the ZIF-Zn nanoparticles were evenly dispersed to obtain a ZIF-Zn@SA solution.
[0073] Take 50g of calcium chloride in a beaker, add 1000mL of ethanol, and stir until the calcium chloride is completely dissolved. The mass concentration of calcium chloride is 50g / L.
[0074] A cylindrical mold with a circumference of 8.45mm and a bottom was inserted into the middle of a cylindrical mold with a circumference of 16.9mm and a bottom. The MOF-Zn@SA solution was then added to the gap between the molds and frozen in liquid nitrogen. The resulting ice solid was then left in the air for a while and the cylindrical mold with a circumference of 8.45mm was peeled off. The ZIF-Zn@SA solution was then injected into the gap and continued to be frozen in liquid nitrogen. The solid was left in the air for a while and the mold was peeled off. After freeze-drying for about 24 hours, it was immersed in an ethanol solution containing calcium chloride for 12 hours and then washed with ethanol several times until no calcium ions (Ca2 + Finally, the concentric rods were obtained by vacuum drying at 40°C for 12 to 24 hours. The MOF-Zn and ZIF-Zn nanoparticles each accounted for 30% by weight.
[0075] V. Effect Evaluation
[0076] Using a filter rod making machine, filter rod samples were prepared based on slim cigarettes (cigarette length 97 mm, circumference 17 mm, filter tip length 30 mm) on the same machine, and acetate filter rods were used as controls. The results of the physical properties test of the cigarette filter rods are shown in Table 1.
[0077] Table 1 Test results of main physical indicators of filter rods
[0078]
[0079] As can be seen from Table 1, compared with the normally produced acetate fiber filter rod, the filter rod prepared by the present invention has no obvious difference in physical indicators.
[0080] Cigarette samples were rolled using the aforementioned filter rods on the same machine. They were then equilibrated for 48 hours at a temperature of (22±2)°C and a relative humidity of (60±5)%. To ensure consistent tobacco content, the prepared cigarette samples were screened for testing using a pressure drop of (design value ±100) Pa, a mass of (design value ±0.02) g, and a filter ventilation rate of (design value ±2)%. Specific test results are shown in Table 2.
[0081] Table 2 Impact of cigarette physical and smoke index test results
[0082]
[0083] As shown in Table 2, compared with cigarettes containing acetate filter rods, both blank sodium alginate filter rods and those containing the porous metal-organic framework (MOF) filter rods significantly reduced tar release and seven representative harmful components in cigarette smoke. Within the range of additive amounts studied, tar release was reduced from 7.6 mg / cig to 3.9 mg / cig, and the cigarette hazard index (H) was reduced from 4.4 to 2.4. This is likely because MOFs and sodium alginate are rich in functional groups such as carboxyl, hydroxyl, and aromatic groups, which can effectively adsorb large amounts of hydrocarbons, oxygen-, nitrogen-, and sulfur-containing compounds through hydrogen bonding, electrostatic interactions, coordination, chelation, and π-π stacking. Furthermore, the hydrogel formed by sodium alginate and calcium ions forms a loose, porous, sponge-like structure after freeze-drying. The numerous and evenly distributed pores and the multi-level pores inherent in the MOF allow for the interception of smoke aerosol particles of varying sizes through pore adsorption and pore confinement, achieving the goal of reducing tar and harm.
[0084] This application uses a sodium alginate-calcium ion cross-linking system to construct a three-dimensional network bio-based skeleton to replace traditional acetate fiber materials, and forms a multifunctional filtration system with a micro-meso-macroporous hierarchical structure through in-situ composite MOF nanoparticles and freeze-drying technology. Experimental data show that the filter rod can significantly reduce harmful components in flue gas, among which the tar release is reduced by 48.7% (from 7.6 mg / stick to 3.9 mg / stick), the hazard index is reduced by 45.5% (from 4.4 to 2.4), and it exhibits broad-spectrum adsorption performance for seven major harmful components such as CO. Its harm reduction mechanism is reflected in the triple synergistic effect: 1) molecular size selective adsorption of MOF nanocrystals; 2) micron-scale pore space confinement effect of the biological skeleton; 3) chemical adsorption of abundant carboxyl / hydroxyl functional groups on the surface of the material. The present invention has significant environmental advantages, uses renewable marine bio-based materials to reduce dependence on wood resources, promotes the low-carbon transformation of the filter rod industry, and has good application prospects.
[0085] Although the present invention has been disclosed above by way of embodiments, they are not intended to limit the present invention. Any person skilled in the art may make various choices and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing a harm reduction filter rod based on a multifunctional metal organic framework, characterized in that: The following steps are involved: (1) Preparation of sodium alginate solution: Weigh sodium alginate and dissolve it in deionized water, stirring until completely dissolved to form a sodium alginate aqueous solution with a mass fraction of 3% to 5%; (2) Preparation of calcium chloride solution: Weigh calcium chloride and dissolve it in ethanol, stirring until completely dissolved to form a calcium chloride ethanol solution with a mass concentration of 30-50 g / L; (3) Preparation of metal organic framework compound + sodium alginate solution: The metal organic framework compound nanoparticles are added to a sodium alginate aqueous solution in batches under 20-30 kHz high-frequency ultrasonic conditions, and ultrasonically dispersed for 30 minutes to form a uniform mixed solution; wherein the mass ratio of the metal organic framework compound to the sodium alginate is: 1-8:
10. (4) Freeze molding: The solution is injected into a cylindrical mold and pre-frozen in a freeze dryer at a temperature range of -25 to -10°C for 1 to 2 hours to form an ice solid. The mold is peeled off after being left at room temperature. The vacuum degree is then adjusted to 60 to 80 Pa, and sublimation drying is performed at 30 to 45°C for 12 to 16 hours. Finally, desorption drying is performed at a temperature range of 45 to 60°C for 6 hours to 11 hours. (5) Freeze-drying and cross-linking: After 24 hours of freeze-drying, the product was immersed in a calcium chloride ethanol solution for cross-linking for 6 to 12 hours, and then washed with ethanol until no Ca2 + The residue is finally dried at 40℃ under vacuum conditions for 12 to 24 hours to obtain the harm-reducing filter stick.
2. The method for preparing a harm reduction filter rod based on a multifunctional metal organic framework according to claim 1, characterized in that: The nanoparticles are MOF-Zn nanoparticles and / or ZIF-Zn nanoparticles.
3. The method for preparing a harm reduction filter rod based on a multifunctional metal organic framework according to claim 2, characterized in that: The preparation method of the MOF-Zn nanoparticles is: A certain amount of 2,5-dihydroxyterephthalic acid and zinc nitrate hexahydrate were dissolved in 100 mL of N,N-dimethylformamide (DMF). After ultrasonic treatment, 5 mL of water was added and the mixture was transferred to a hydrothermal autoclave for reaction at 110-120°C for 24 hours. After cooling, the mixture was washed with DMF and methanol three times each, then soaked in methanol for three days. Finally, the mixture was vacuum-dried at 150°C for one hour. The molar ratio of zinc nitrate to 2,5-dihydroxyterephthalic acid was 1:3-5.
4. The method for preparing a harm reduction filter rod based on a multifunctional metal organic framework according to claim 2, characterized in that: The preparation method of the ZIF-Zn nanoparticles is: A certain amount of zinc nitrate hexahydrate and 2-methylimidazole were weighed and dissolved in water and methanol respectively. The two solutions were mixed under stirring and reacted for 3 hours. The product was collected by centrifugation, washed with water and methanol three times each, and dried in vacuo at 85°C for 1 hour. The molar ratio of zinc nitrate to 2-methylimidazole was 1:2-8, and the volume ratio of water to methanol was 1:
10.
5. A harm reduction filter rod based on a multifunctional metal organic framework, characterized in that: The harm reduction filter rod is prepared according to the preparation method according to any one of claims 1 to 4.
6. A cigarette product, characterized in that: Contains the harm reduction filter stick described in claim 5.
7. Use of the harm-reducing filter rod according to claim 5 in the preparation of low-tar cigarettes.